Managing Liberalization and Globalization in Rural China: Trends in Rural Labour Allocation, Income and Inequality - Dong, Xiao-Yuan; Bowles, Paul; Chang, Hongqin (Global Labour Journal, 2009)
China’s integration into the global economy, while rapid, has been managed as part of a wider liberalization process. The structural changes in the rural economy arising from these twin processes have led to widening intra-rural inequalities. To address these, the central leadership has, in Polanyian manner, moved to counter some of the adverse effects of liberalization and globalization. We discuss this dynamic as it has affected rural China. We analyze results from a national data set covering the period 1991-2006 to assess the extent to which the state has been successful in protecting society from the advance of market forces. We find positive outcomes in terms of real earnings growth and poverty reduction but negative outcomes in terms of the rise in open unemployment and in terms of increasing intra-rural income inequality, although this was noticeably more pronounced in the 1991-2000 period than in the 2000-2006 period when more active government redistributive mechanisms were in place.
Economics
Keywords: globalization; income inequality; labor studies; labour allocation; labour studies; liberalization; rural China

L’« institution » selon Karl Polanyi. Fondements et mise en perspective contemporaine - Maucourant, Jérôme; Plociniczak, Sébastien (Tracés. Revue de Sciences humaines, 2009)
Depuis les années soixante-dix, certains économistes ont tenté de répondre aux difficultés de plus en plus nombreuses qu’ils rencontraient en réélaborant le concept d’institution. Cette tentative « néo-institutionnaliste » fut porteuse de malentendus. L’autonomisation progressive de l’économie comme savoir s’était, en effet, construite sur l’occultation délibérée de toutes sortes de fondements extra-économiques. La quête de tels fondements, dans l’intention d’asseoir scientifiquement la conna...
Economics
Keywords: MALTHUS; T. R.; RICARDO; David; institutionalist approach

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Economics; Anthropology
Keywords: Athenian supremacy; Greece; 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies; Economics
Keywords: Polanyi; interventionism; markets; pendulum

Le differenti ibridazioni di risorse nelle imprese sociali europee - Gardin, Laurent (The various types of resources mobilised by European social enterprises., 2009)
The objective of this paper is to analyse, on the basis of the substantive definition of the economy (elaborated in the footsteps of Polanyi), the various types of resources mobilised by European social enterprises. European social enterprises use a complex mix of resources based on four types of economic relations: the market, redistribution, the socio-politically embedded market, and the reciprocity. A European typology of Work Integration Social Enterprise (WISEs) is put forward, in order to understand these enterprises' dynamic across national borders. (English)
Sociology; Economics
Keywords: Europe; business enterprises; distribution; economic theory; markets; reciprocity (commerce); social enterprise; socioeconomics

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Economics; Business
Keywords: commodification; commodification of nature

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Economics; Sociology
Keywords: appropriation; destructive mode of coordination; social integration

The Social Economics of Neoliberal Globalization - Stanfield, James Ronald; Carroll, Michael C. (Forum for Social Economics, 2009)
The recent period of intensive and extensive development of global economic integration, or globalization, has reached a crossroads. The regime of the neoliberal Great Capitalist Restoration is not sustainable and fundamental governance changes must be made. This paper adds perspective to the choices that must be made at this critical juncture of the global social economy by applying the master concepts of Schumpeter's Creative Destruction and Polanyi's Protective Response.
Economics
Keywords: capitalist systems: political economy; global social economy; international economic order; protective response; social economy

Karl Polanyi et La Pédagogie De L'incohérence - Gazier, Bernard; Mendell, Margie (Annals of Public and Cooperative Economics, 2009)
Cet article vise à examiner de manière critique et constructive l'actualité de la pensée de Karl Polanyi pour comprendre le développement de l'économie plurielle au XXIe siècle et pour agir sur celui-ci. Il montre la très grande actualité de cette pensée, ainsi que la nécessité de s'intéresser à l'œuvre entière de Karl Polanyi, et pas seulement à«La grande transformation». Partant des usages multiples du concept d'encastrement et de désencastrement, il relie les propositions inspirées par Karl Polanyi sur «le processus institué de démocratisation économique»à des développements récents tant pratiques que théoriques: les «>marchés transitionnels du travail» et la «nouvelle finance publique». ENG: The aim of this article is to examine critically and constructively the current state of Karl Polanyi's thinking in order to understand and act on the development of the pluralist economy in the twenty-first century. It shows the very topicality of this thought, as well as the need to take an interest in the entire work of Karl Polanyi, not just "The great transformation". Starting from the multiple uses of the concept of embedding and disencing, he links the proposals inspired by Karl Polanyi on "the instituted process of economic democratization" to recent practical and theoretical developments: "transitional labor markets" and " New public finance ".
Economics
Keywords: economic democratization; instituted economic process; new public finance; pluralist economy; transitional labor markets; transitional labour markets

Polanyi, lecteur de Marx - Maucourant, Jérôme (2009)
En premier lieu, c'est la critique du capitalisme et du fascisme comme la prolongation toujours possible de celui-ci qui nous semble devoir être traitée. L'interprétation chrétienne du marxisme, à laquelle se livre Polanyi, est une façon de comprendre la condition d'étrangeté qu'éprouve l'homme moderne face à lui-même ; cette interprétation permet aussi de voir dans le fascisme la négation même du socle judéo-chrétien qui fonde en Occident la communauté humaine authentique. En second lieu, nous aborderons la question du contenu et de la construction du socialisme. Si, pour Polanyi, le socialisme est la réponse chrétienne aux défis posés par l'âge industriel, en revanche, la démocratie n'est pas une simple "superstructure" du capitalisme : une ambiguïté de l'œuvre de Marx est alors soulignée. Le socialisme, selon Polanyi, est l'extension du constitutionnalisme à la sphère de l'économie. Aux mirages de l'économie de commandement, Polanyi, dès 1922, oppose déjà la nécessité éthique d'une économie décentralisée impliquant la responsabilité des producteurs-associés. D'ailleurs, la signification du socialisme semble liée à la façon politique de l'instituer. Polanyi est hostile à la doctrine selon laquelle la stricte préservation de l'intérêt économique d'une classe sociale est à même d'assurer sa sauvegarde à long terme, car la lutte de classes doit tenir compte d'enjeux sociaux globaux. D'une façon générale, contre toute forme de déterminisme, singulièrement celui de la IIième internationale, Polanyi oppose la valeur de ce qui est dû aux choix conscients et responsables. Enfin, nous présenterons les débats anthropologiques qui marquèrent la seconde grande période de l'itinéraire de Polanyi. Jusqu'en 1936, il est possible d'inclure Polanyi dans le courant austro-marxiste ; après 1950, Polanyi critique l'idéologie économique qui caractérise nombre d'aspects du travail des sciences sociales. Les figures du travail de Marx qui sont inspirées par l'économisme occidental sont dénoncées par Polanyi ; mais Polanyi lui-même et certains membres de son école distinguent bien Marx d'Engels. Il n'en reste pas moins que les investigations de Polanyi sont une façon de conserver certains acquis du travail de Marx tout en s'émancipant du cadre de la dialectique. Popper lui-même reconnaît une dette envers Polanyi : celui-ci lui aurait montré les vertus d'un "nominalisme méthodologique" pour les sciences sociales dans les années 20. C'est cette même attitude qui inspire le programme Columbia des années 50 et qui provoque le rejet par certains marxistes de la méthode dite "substantive". Mais, ce que rejette Polanyi, ce n'est pas l'intérêt de l'analyse marxiste pour le capitalisme de son époque, c'est plutôt l'extension aux sociétés non-modernes de concepts imprégnés par la modernité ; c'est enfin, le refus de toute "loi" de développement social. Par où Polanyi, sans être cette façon d'anti-Marx à l'usage de "radicaux" pour les temps post-modernes, se révèle aussi pertinent qu'actuel. First, this is the critique of capitalism and fascism as the always possible extension of it seems we have to be treated. The Christian interpretation of Marxism by Polanyi is a way of understanding the condition of strangeness experienced by modern man in front of himself; This interpretation also makes it possible to see in fascism the very negation of the Jewish-Christian base which founds the authentic human community in the West. Second, we will address the question of the content and construction of socialism. If, for Polanyi, socialism is the Christian response to the challenges posed by the industrial age, democracy, on the other hand, is not a simple "superstructure" of capitalism: an ambiguity of Marx's work is underlined. Socialism, according to Polanyi, is the extension of constitutionalism to the sphere of the economy. To the mirages of the economy of command, Polanyi, already in 1922, already opposes the ethical necessity of a decentralized economy involving the responsibility of the associate producers. Moreover, the meaning of socialism seems to be linked to the political way of instituting it. Polanyi is hostile to the doctrine that the strict preservation of the economic interest of a social class is capable of ensuring its long-term safeguard, since the class struggle must take account of global social issues. In a general way, against all forms of determinism, particularly that of the Second International, Polanyi opposes the value of what is due to conscious and responsible choices. Finally, we will present the anthropological debates that marked the second major period of Polanyi's itinerary. Until 1936, it was possible to include Polanyi in the Austro-Marxist current; After 1950, Polanyi criticized the economic ideology that characterizes many aspects of social science work. The figures of Marx's work which are inspired by Western economism are denounced by Polanyi; But Polanyi himself and some members of his school distinguished Marx from Engels. The fact remains that Polanyi's investigations are a way of preserving certain of the achievements of Marx's work, while emancipating himself from the framework of the dialectic. Popper himself acknowledged a debt owed to Polanyi, who would have shown him the virtues of a "methodological nominalism" for the social sciences in the 1920s. It was this attitude that inspired the Columbia program of the 1950s, Provokes the rejection by certain Marxists of the so-called "substantive" method. But what Polanyi rejects is not the interest of Marxist analysis for the capitalism of his time, but rather the extension to modern societies of concepts imbued with modernity; Finally, the refusal of any "law" of social development. By which Polanyi, without being this way of anti-Marx to the use of "radicals" for the post-modern times, is as relevant as it is actual. Working paper or preprint
Economics; Sociology
Keywords: MARX; Karl; 1818-1883; communism; communisme; fascism; fascisme; matérialisme historique; socialism; totalitarisme; vitalisme

Keynes’s Stimulus, Polanyi’s Movement - Milberg, William S. (Harvard College Economic Review, 2009)
The foundations of Keynes and the principles of Polanyi offer insight into crafting a new American economy
Economics
Keywords: KEYNES; John Maynard; 1883-1946; economics

The Financialization of Modern Economies in Monetary Circuit Theory - Pilkington, Marc (The Political Economy of Monetary Circuits: Tradition and Change in Post-Keynesian Economics, 2009)
Economics
Keywords: Canada: 1913-; banks; depository institutions; economic history: financial markets and institutions: United States; government and the monetary system; haute finance; history of economic thought: individuals; household saving; international financial markets; micro finance institutions; monetary policy; central banking; and the supply of money and credit; monetary systems; mortgages; payment systems; personal finance; regimes; standards

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Sociology; Economics
Keywords: double movement; economic sociology; neoliberalism

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Economics
Keywords: environemntal politics; environmental value; redistribution